Linking signaling dynamics and cell fate decisions through single-cell imaging: evidence and challenges - Bonsignore, Fulvio; Pozzi, Sara; Aloi, Erika; Mazza, Davide; Zambrano, Samuel (Frontiers in Cell and Developmental Biology, 2025)
Our ever-growing capacity to observe dynamic processes at the single-cell level has highlighted how cells use complex signaling dynamics to provide adequate responses to intra- and extracellular cues. Specifically, there is increasing evidence that signaling dynamics can be functional in determining cell fate decisions. In this work, we provide an overview of the growing body of evidence supporting this idea across diverse biological contexts—including immune responses, reactions to DNA damage and growth factors, and embryonic development. In doing so, we aim to provide a precise conceptualization of what is meant when we say that signaling dynamics can determine cell fate, a unifying view of the methodologies used to sustain this claim and to identify some of the existing gaps in our mechanistic understanding of this process. We believe that the body of work hereby described strongly supports the importance of considering the temporal dimension of signaling when seeking to understand how cellular responses are regulated.